SINGO LARAS” KARAWITAN EXTRACURRICULAR: A QUALITATIVE STUDY ON THE DEVELOPMENT OF CIVIC DIMENSIONS IN PRIMARY EDUCATION - Astuti; Riyadi; Matsuri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze student participation in karawitan extracurricular activities as an effort to develop the citizenship dimension in elementary schools. The study uses a descriptive qualitative approach with a single case study design at SD Negeri Singodutan, Wonogiri, involving 20 fifth-grade students participating in the 'Singo Laras' karawitan extracurricular program. Data were collected through participatory observation, in-depth interviews, and documentation, and then analyzed using Miles and Huberman's interactive model with triangulation techniques to ensure data validity. The results of the study indicate that student participation is formed through active involvement in the structured stages of activities (preparation, implementation, and closing), repeated practice, as well as collaborative interaction among students and guidance from instructors. This participation contributes to the development of citizenship dimensions, which include the values of mutual cooperation, responsibility, discipline, tolerance, and social roles. These findings confirm that extracurricular activities based on local culture, particularly karawitan, function as an effective contextual learning medium for internalizing civic values through authentic social experiences. This study implies that the integration of experiential and local culture-based learning can strengthen the implementation of civic education and support the reinforcement of the Pancasila Student Profile.